Status fungi mikoriza arbuskula pada berbagai sistem pengelolaan dan umur tanaman kelapa sawit - Rossy A. Arman; Fikrinda Fikrinda; Muyassir Muyassir; Ashabul Anhar; N. F. Mardatin; Teti Arabia (Jurnal Floratek, 2015)
Status of Arbuscular Mycorrhizal Fungi in Different Farming Systems and Age of Oil PalmABSTRACT. A survey was conducted to determine the Arbuscular Mycorrhiza Fungi (AMF) spore population in rhizosphere soils and its root colonization of oil palm belonging to four age class (2-3months, 2 years, 7 years, and 10 years) at PTPN I Estate plantation and smallholder farmer plantation in Cot Girek Aceh Utara. The methods used were direct isolation. The result showed that there were 14 species of AMF belongs to genus Glomus identified according to spore morphology, eight species at PTPN I and six species at smallholder oil palm plantation. AMF spore density at PTPN I and smallholder oil palm was 17.35 and 17.80 spore per 50g soil, respectively. Oil palm at 7 years old resulted in better AMF population, i.e. 53,7 spore per 50 g Soil. AMF colonization at oil palm rhizospere in both farming systems were low, i.e. 5.4% (PTPN I) and 2.9% (smallholder). Farming system and age of oil palm influenced the AMF population and root colonization, Spore density did not positively correlate with root colonization at different farming systems and age of oil palm.